2018
DOI: 10.1016/j.brat.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Is less more? A randomized comparison of home practice time in a mind-body program

Abstract: Home practice is a major component of mind-body programs, yet little is known about how to optimize the amount of prescribed home practice in order to achieve an effective “dose” of practice while minimizing participant burden. This study tested how varying the amount of home practice in a mind-body program impacts compliance and stress reduction, and whether prescribing a flexible home practice schedule increases compliance. Eighty-four stressed participants undergoing a 12-week yoga program were randomized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…This finding highlights an important distinction between Kripalu yoga's utility as a stress management resource versus a standalone clinical intervention. Even a single session of yoga practice has demonstrated significant pre–post effects on positive and negative affective experience (Park et al, 2020), and regular, repeated yoga practice has been associated with positive stress‐related outcomes (Gard et al, 2014; Greenberg et al, 2018). In contrast to talk‐based cognitive behavioural therapies that provide explicit discussion of disordered emotion regulation abilities (Hofmann, Sawyer, Fang, & Asnaani, 2012), mechanisms of yoga interventions such as Kripalu may act much more quickly upon perceptions of acute stress by directing non‐judgemental attention towards physical experience, and thus require different methods of assessing change in real time (e.g., ecological momentary assessment, measurement of affective states pre‐ and post‐practice).…”
Section: Discussionmentioning
confidence: 99%
“…This finding highlights an important distinction between Kripalu yoga's utility as a stress management resource versus a standalone clinical intervention. Even a single session of yoga practice has demonstrated significant pre–post effects on positive and negative affective experience (Park et al, 2020), and regular, repeated yoga practice has been associated with positive stress‐related outcomes (Gard et al, 2014; Greenberg et al, 2018). In contrast to talk‐based cognitive behavioural therapies that provide explicit discussion of disordered emotion regulation abilities (Hofmann, Sawyer, Fang, & Asnaani, 2012), mechanisms of yoga interventions such as Kripalu may act much more quickly upon perceptions of acute stress by directing non‐judgemental attention towards physical experience, and thus require different methods of assessing change in real time (e.g., ecological momentary assessment, measurement of affective states pre‐ and post‐practice).…”
Section: Discussionmentioning
confidence: 99%
“…per day three days per week). Detail on home practice adherence and frequency can be viewed in our published work (Greenberg et al, 2018 ). Because the present study observed no group differences on the variables of interest in this study, the reported analyses analyze all participants as one group.…”
Section: Methodsmentioning
confidence: 99%
“…mindfulness, self-compassion) to decrease physiological arousal and enhance well-being. Details on the intervention, including the three home practice conditions, can be reviewed in our prior work (Braun et al, 2021 ; Greenberg et al, 2018 ). Broadly, the 12-week intervention comprised two segments: first, a manualized protocol consisting of eight weekly 2-hour sessions on “hatha” (since technically the entire intervention, including philosophy components, were yoga), whereas the 90-min classes were hatha yoga practices only.…”
Section: Methodsmentioning
confidence: 99%
“…Dosage was positively associated with decreases in systolic blood pressure at both 3- and 6-month follow-up. Greenberg et al (2018) randomly assigned 84 stressed participants to three home practice conditions (60, 150, or 240 min per week) within a yoga-based mind–body intervention, finding significant stress reduction only within the high dose condition (although no time by group differences between groups).…”
mentioning
confidence: 99%